Determinants of carrying capacity for ecotourism in wildlife sanctuary area a case study of Ligawasan Marsh bird sanctuary - Dimaucom, Anwar A. (School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
Ecotourism development and environmental conservation has become more and more intertwined in recent years. In fact, the two concepts have been at opposite sides of the same coin in as much as sustainable development and conservation of protected areas is concerned. Both framers of ecotourism and conservation plans and tourism professionals have recognized the role of sustainable ecotourism planning in the effective implementation of conservation efforts in protected areas. However, for ecotourism to fulfill its potential and generate sustainable benefits, protected areas must implement a planning framework to guide and manage the activity. Hence, the need for strategies for critical elements of ecotourism management, such as zoning, visitor impact monitoring, visitor site design and management, income generation mechanisms, infrastructure and identifying the carrying capacity of the site subject to ecotourism development.In the case of Ligawasan Marsh in Central Mindanao, a recognized protected area in need of critical conservation efforts, identification of the determinants of carrying capacity for ecotourism is imperative to institute sound conservation measures through sustainable ecotourism development. Although the results of the perception survey conducted in the study among local communities reveal that the current ecotourism program in Ligawasan Marsh has brought to the local communities including augmentation of income, increase in job opportunities and restoration of the unique facets of the Marsh. Moreover, positive impacts were articulated including promotion of environmental protection and improvement of the quality of the living environment. On the other hand, adverse effects were also identified such as increased volume of garbage and waste, noise problems and disruption of the people's daily life . The local residents, however, indicated their willingness and commitment in contributing to the protection of their living environment in order to enhance the role of ecotourism in their communities.To ensure environmental protection, the Study recommends the implementation of the ring management system of areas within Ligawasan Marsh.